Screening, production and biochemical characterization of a new fibrinolytic enzyme produced by Streptomyces sp. (Streptomycetaceae) isolated from Amazonian lichens - Silva, Germana Michelle de Medeiros e (2016)
Thrombosis is a pathophysiological disorder caused by accumulation of fibrin in the blood. Fibrinolytic proteases with potent thrombolytic activity have been produced by diverse microbial sources. Considering the microbial biodiversity of the Amazon region, this study aimed at the screening, production and biochemical characterization of a fibrinolytic enzyme produced by Streptomyces sp. isolated from Amazonian lichens. The strain Streptomyces DPUA1576 showed the highest fibrinolytic activity, which was 283 mm2. Three variables at two levels were used to assess their effects on the fibrinolytic production. The parameters studied were agitation (0.28 - 1.12 g), temperature (28 - 36 ºC) and pH (6.0 - 8.0); all of them had significant effects on the fibrinolytic production. The maximum fibrinolytic activity (304 mm2) was observed at 1.12 g, 28 ºC, and pH of 8.0. The crude extract of the fermentation broth was used to assess the biochemical properties of the enzyme. Protease and fibrinolytic activities were stable during 6 h, at a pH ranging from 6.8 to 8.4 and 5.8 to 9.2, respectively. Optimum temperature for protease activity ranged between 35 and 55 °C, while the highest fibrinolytic activity was observed at 45 ºC. Proteolytic activity was inhibited by Cu2+ and Co2+ ions, phenylmethylsulfonyl fluoride (PMSF) and pepstatin A, which suggests that the enzyme is a serine protease. Enzymatic extract cleaved fibrinogen at the subunits A-chain, A-chain, and -chain. The results indicated that Streptomyces sp. DPUA 1576 produces enzymes with fibrinolytic and fibrinogenolytic activity, enzymes with an important application in the pharmaceutical industry.